Pengaruh Kompensasi, Motivasi dan Kepuasan Kerja Terhadap Turnover Intention Karyawan di PT. XY Plant Cibitung - Tri Mulyani Kartini; Sri Wahyuningsih; Rismawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human Resources (HR) play an important role in the company, with employee performance influenced by fair compensation and a supportive work environment. A mismatch in these two aspects can trigger turnover intention. Compensation, motivation and job satisfaction are interrelated in improving performance, while good HR policies can reduce turnover and retain quality employees. This research aims to analyze the influence of Compensation, Motivation and Job Satisfaction on employee turnover intention at PT. XY Plant Cibitung. Data was collected through a questionnaire with quantitative methods and a sample of 40 people. Multiple linear regression analysis is used to test the hypothesis. The research results show that compensation (sig 0.004), motivation (sig 0.038), and job satisfaction (sig 0.001) have a significant effect on employee turnover intention. To reduce turnover intention, companies are advised to increase compensation, provide good motivation, and manage employee job satisfaction.